Consumer ethnocentrism vs. intercultural competence as moderators in intercultural service encounters - Sharma, Piyush; Wu, Z. (Emerald Group Publishing, 2015)
Purpose – This paper aims to explore the moderating effects of consumer ethnocentrism and intercultural competence on the impact of service outcome and perceived cultural distance, respectively, on interaction comfort and perceived service quality in intercultural service encounters. Design/methodology/approach – A 2 X 2 between-subjects experimental design with university students was used, using service encounter scenarios to manipulate service outcome (failure or success) and photos of service employees to manipulate perceived cultural distance (low vs high). Findings – As hypothesized, the impact of service outcome on interaction comfort and perceived service quality is moderated negatively by consumer ethnocentrism, whereas the impact of perceived cultural distance is moderated positively by intercultural competence. Research limitations/implications – An experimental design using imaginary service scenarios was used in a single service context (i.e. restaurant) with university students as participants, which may restrict the generalizability of our findings. Practical implications – Managers in service firms with multicultural customers should try to recruit service employees with high intercultural competence and low consumer ethnocentrism. They should also develop employee training programs that help minimize the adverse impact of these variables on interaction comfort and service quality in intercultural service encounters. Originality/value – This paper extends prior research by exploring the moderating effects of consumer ethnocentrism and intercultural competence on the direct and indirect effects of service outcome and perceived cultural distance on interaction comfort, service quality and satisfaction.